2016
DOI: 10.1038/srep29717
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiazinethione is a potent preclinical candidate for the treatment of drug-resistant tuberculosis

Abstract: New chemotherapeutic compounds are needed to combat multidrug-resistant Mycobacterium tuberculosis (Mtb), which remains a serious public-health challenge. Decaprenylphosphoryl-β-D-ribose 2′-epimerase (DprE1 enzyme) has been characterized as an attractive therapeutic target to address this urgent demand. Herein, we have identified a new class of DprE1 inhibitors benzothiazinethiones as antitubercular agents. Benzothiazinethione analogue SKLB-TB1001 exhibited excellent activity against Mtb in the Microplate Alam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Gao et al. identified an S ‐acetal BTZ analogue ( 251 ) as being more potent in vitro than BTZ‐038, while similarly a thioamide (SKLB‐TB1001, 252 ) analogue was identified having superior in vivo activity in acute murine models of infection than 248 coupled to good bioavailability and safety profiles . In an effort to improve the pharmacokinetic properties of BTZ compounds, Karoli et al .…”
Section: Tuberculosismentioning
confidence: 99%
“…Gao et al. identified an S ‐acetal BTZ analogue ( 251 ) as being more potent in vitro than BTZ‐038, while similarly a thioamide (SKLB‐TB1001, 252 ) analogue was identified having superior in vivo activity in acute murine models of infection than 248 coupled to good bioavailability and safety profiles . In an effort to improve the pharmacokinetic properties of BTZ compounds, Karoli et al .…”
Section: Tuberculosismentioning
confidence: 99%
“…area under the concentration-time curve (AUC) with the intravenous (i.v.) AUC of SKLB-TB1001 in plasma over time showed an apparent oral bioavailability of 44.4% (50-mg/kg dose), which was significantly higher than that of BTZ043 (F ϭ 29.5%) (10). These results indicated that SKLB-TB1001 had adequate PK properties for in vivo efficacy.…”
Section: Resultsmentioning
confidence: 82%
“…We recently reported a new benzothiazinethione, SKLB-TB1001, which had promising antitubercular potency against drug-sensitive, as well as MDR and XDR, M. tuberculosis in vitro at nanomolar concentrations. In addition, additive to synergistic interactions were observed when SKLB-TB1001 was combined with other TB drugs in checkerboard assays (10,11). However, although SKLB-TB1001 showed excellent antitubercular efficacy in vitro, it was less effective in a murine model in further studies.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Tiwari et al and Gao et al have worked on modifying the BTZ scaffold and have proposed some potent DprE1 inhibitors through their structure–activity relationship study. Some of these compounds such as SKLB‐TB1001 are potent preclinical candidates in the treatment of drug‐resistant TB.…”
Section: Introductionmentioning
confidence: 99%